KEBIASAAN MAKAN HIU KEJEN (Carcharinus falciformis): STUDI KASUS PENDARATAN HIU DI PPP MUNCAR JAWA TIMUR (Feeding habit of Silky Shark (Carcharinus falciformis): Case Study of Landing Shark in Muncar Coastal Fishing Port East Java) - Benaya M. Simeon; Mulyono S. Baskoro; Am Azbas Taurusman; Dwi A. Gautama (Bogor Agricultural University, 2015)
ABSTRACTIndonesia is the biggest country which produced shark in the world. Muncar Coastal Fishing Port, Banyuwangi, is a shark fishing center in East Java. Caught sharks were dominated by silky shark (Carcharinus falciformis). Primary data collected by in situ sampling and stomach content analysis. Stomach content was collected by sectio. It preserved by 10% formaline in coolbox. Silky shark had caught by shark long line and gillnet. Shark is the fish target of longline and by-catch of gillnet. Silky shark preys were grouper fish (Epinephelus sp.) as main prey and squid (Loligo sp.), beltfish (Trichiurus lepturus), sardine (Sardinella lemuru) as complementary preys. Based on stomach content analysis, silky shark was identified on 4.7 trophic level. Silky shark preys were grouper on trophic level 4.1, squid, beltfish on trophic level 4.4, sardine on trophic level 2.1. Silky shark as apex predator could be found in Bali Strait and Makassar Strait, which it classified as fertility water. The existence of silky sharks whicht prey fish in several trophic level layers made silky shark as one of the key species in Bali Strait and Makassar Strait. Catching sharks will have implications for trophic level is high or low.Keywords: feeding habit, silky shark, trophic level——-ABSTRAKIndonesia merupakan negara penghasil hiu terbesar di dunia. PPP Muncar, Banyuwangi merupakan salah satu pusat penangkapan hiu di Jawa Timur. Hiu yang tertangkap oleh nelayan didominasi oleh hiu kejen (Carcharinus falciformis). Data primer didapatkan dari pengambilan sampel dan analisis isi lambung. Isi lambung didapatkan dari proses pembedahan. Isi lambung diawetkan dalam formalin 10% dalam coolbox. Hiu kejen tertangkap menggunakan rawai dan gillnet. Hiu menjadi ikan target pada alat tangkap rawai dan by-catch pada gillnet. Mangsa hiu kejen adalah kerapu sebagai makanan utama dan lemuru, cumi-cumi, layur merupakan makanan pelengkap. Hiu kejen (C.falciformis) yang tertangkap di Selat Bali berada pada trofik level 4,7. Mangsa utama hiu kejen adalah kerapu (trofik level 4,1) dan mangsa pelengkap lemuru (trofik level 2,1), layur (trofik level 4,4) dan cumi-cumi. Hiu kejen sebagai salah satu apex predator dapat ditemukan di Selat Bali maupun Selat Makassar yang memiliki kesuburan tinggi. Keberadaan hiu kejen yang memangsa beberapa ikan di beberapa lapisan trofik level menjadikan hiu kejen sebagai salah satu spesies kunci di perairan Selat Bali dan Selat Makassar. Penangkapan hiu akan memberi implikasi terhadap trofik level yang tinggi maupun rendah.Kata kunci: kebiasaan makan, hiu kejen, trofik level